PENGARUH PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI ALFAMART JATIMAKMUR PONDOK GEDE BEKASI - Margareta Jun; Arief Syah Safrianto (Jurnal Ekonomi dan Industri, 2025)
The purpose of this study is to analyze the influence of promotion and location on purchasing decisions at Alfamart Jatimakmur Pondok Gede Bekasi. This study uses a quantitative approach. The population in this study were customers of Alfamart Jatimakmur Pondok Gede Bekasi. The analysis method uses multiple and simple linear regression. The results of the study show that both simple and joint promotion and location have a positive and significant influence on purchasing decisions at Alfamart Jatimakmur Pondok Gede Bekasi.